2016
DOI: 10.1152/ajpendo.00441.2015
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a proapoptotic gene (BBC3) in islet injury mediated by cold preservation and rewarming

Abstract: Long-term pancreatic cold ischemia contributes to decreased islet number and viability after isolation and culture, leading to poor islet transplantation outcome in patients with type 1 diabetes. In this study, we examined mechanisms of pancreatic cold preservation and rewarming-induced injury by interrogating the proapoptotic gene BBC3/Bbc3, also known as Puma (p53 upregulated modulator of apoptosis), using three experimental models: 1) bioluminescence imaging of isolated luciferase-transgenic (“Firefly”) Lew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Inflammation-related gene expressions ( IL1B and TNF ) ( 27 , 28 ) showed the trend of lower inflammation in microwells compared to flat dishes though not statistically significant ( Supplementary Figure 5 ). Expressions of apoptosis-related genes ( BBC3 and FASLG ) ( 29 , 30 ) and necrosis-related genes ( HMGB1 ) ( 31 ) in flat dishes and microwells did not demonstrate the primary cause of cell death; rather, they were donor-dependent. Quantification of Live/Dead stained cultured islets demonstrated that the microwell dish significantly improved the viability compared to the flat dish (60.8% vs. 86.2%, P = 0.0196; Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation-related gene expressions ( IL1B and TNF ) ( 27 , 28 ) showed the trend of lower inflammation in microwells compared to flat dishes though not statistically significant ( Supplementary Figure 5 ). Expressions of apoptosis-related genes ( BBC3 and FASLG ) ( 29 , 30 ) and necrosis-related genes ( HMGB1 ) ( 31 ) in flat dishes and microwells did not demonstrate the primary cause of cell death; rather, they were donor-dependent. Quantification of Live/Dead stained cultured islets demonstrated that the microwell dish significantly improved the viability compared to the flat dish (60.8% vs. 86.2%, P = 0.0196; Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…The viability index of rat islets after 72 h of cold preservation in UW solution supplemented with 500 µg/mL DAFP-1 (1.17 ± 0.08) was significantly higher than islets preserved in UW solution alone control ( Figure 5 B). It is known that the cold preservation-mediated islet injury is manifested during the rewarming of the islets [ 34 , 43 ]. Therefore, we further assessed the recovery and viability of islets after cold preservation followed by rewarming.…”
Section: Resultsmentioning
confidence: 99%
“…PUMA activation is known to be involved in p53-mediated apoptosis 36,37 and, interestingly, we observed an increase in PUMA (BBC3) expression in rat islets incubated in vitro under hypoxia and transplanted to immunodeficient mice. Other studies reported that PUMA is involved in cell death in human and rodent islets exposed to various insults [38][39][40][41][42][43] . A correlation has also been reported between PUMA gene expression and dysfunction of the grafted human islets in immunodeficient mice 38 .…”
Section: Discussionmentioning
confidence: 98%